KINERJA SURAT BERHARGA SETELAH INITIAL PUBLIC OFFERING - Umi Murtini (Fakultas Bisnis UKDW, 2005)
This study observes the pedormance of stock, shortierm and long-term in Jakarta Stock Exchange (BEJ). Sample data taken from firm that hove done IPO since the January 1990 untit December 2003, amount sample that used as much 255 firms. The daily abnormal return used as proxy perlormance by using Market-Adjusted Return Abnormal Model (Aggwwal 993). Short-term pedormance is based on a share performance atter, one day,' one month, 2 month and 3 month, Long-term perfonnance is b,osed on performance during 24 month. The result tests of one sampte t-test indicate that in short-term, cnerage abnormal return ore positive equal to i,8, 83 %. This result consistent with the previous research that performance in short-term experience, of the under pricing, Abnormal relurn that resuked in long term are arcrage negative equal to 21, 44%. This study Jinds the consistent phenomenon underperformance on a long term. And then the results of paired comparisont-test indicate that the short-term performance,is better lhqnlong-range performance, at level I %o.signtficance.Keywords: t Initiol Pubtic Offering, Performace of IPO, Abnormitl'Return, Underpricing and Underperform)